The Sexy Self-Representation of Indonesian Internet Influencer on Social Media - Kurniawan, Yusuf; Kristina, Diah; Primasita, Fitria Akhmerti; Kusciati, Karunia Purna; Wardani, Dike Kusuma (Humanus, 2024)
This research aims to examine the self-representation of sensuous female influencers in Indonesia, specifically a 20-year-old female Javanese influencer who lives in Surakarta, on Instagram, and how the influencer publicly presents herself in front of the audience. Relying on Goffman’s Dramaturgical approach, this study provides thorough insights into the frontstage and backstage behavior of the sensuous female influencer and the representation of the influencer on the frontstage. Employing Charles Sanders Peirce’s semiotic triadic model (1931), the data obtained from Instagram were analyzed by understanding the representamen, the interpretant, and the object of the data. Then, to gain a more detailed understanding, the data collected from in-depth interviews were also scrutinized. This study shows that there is an act of rebellion of being against society's norms of modesty as the influencer constantly acts in a sexualized manner in public and daily activity. While previous studies mostly examine the phenomenon of the sexualized manner of women in hyper-sexualized cultures/Western cultures, this study provides an understanding of the sexualized manner of a sensuous Javanese female influencer in the area where people do not find self-sexualization behavior as common or prevalent.